2013
DOI: 10.1002/chem.201302679
|View full text |Cite
|
Sign up to set email alerts
|

Construction of Shallow Surface States through Light Ni Doping for High‐Efficiency Photocatalytic Hydrogen Production of CdS Nanocrystals

Abstract: Ni-doped CdS nanowires were synthesized by a simple one-step method. X-ray diffraction, X-ray photoelectron spectroscopy, and photoluminescence spectroscopy confirmed that light Ni doping can form shallow surface states due to the presence of substitutional Ni ions, and heavy Ni doping can form deep surface states due to the presence of interstitial Ni ions. Surface photovoltage spectroscopy and transient photovoltage measurements revealed that the shallow surface states can prolong the lifetime of the photoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
45
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 95 publications
(48 citation statements)
references
References 50 publications
3
45
0
Order By: Relevance
“…The PL spectra shown in these figures illustrated three distinct emission mechanisms: direct recombination of the photogenerated electrons and holes, recombination of the excitons bound to certain shallow trapping states, and transitions involving sub-band gap energy states due to the defects in the lattice. As reported [11,34]; the PL bands at~530 nm (2.36 eV) and 547 nm (2.28 eV) were ascribed to band edge emission, i.e. the direct recombination of the photogenerated electrons and holes from the i n t e r n a t i o n a l j o u r n a l o f h y d r o g e n e n e r g y 4 0 ( 2 0 1 5 ) 8 6 9 5 e8 7 0 5 conduction and valence bands.…”
Section: Photoluminescence (Pl) Spectramentioning
confidence: 59%
See 3 more Smart Citations
“…The PL spectra shown in these figures illustrated three distinct emission mechanisms: direct recombination of the photogenerated electrons and holes, recombination of the excitons bound to certain shallow trapping states, and transitions involving sub-band gap energy states due to the defects in the lattice. As reported [11,34]; the PL bands at~530 nm (2.36 eV) and 547 nm (2.28 eV) were ascribed to band edge emission, i.e. the direct recombination of the photogenerated electrons and holes from the i n t e r n a t i o n a l j o u r n a l o f h y d r o g e n e n e r g y 4 0 ( 2 0 1 5 ) 8 6 9 5 e8 7 0 5 conduction and valence bands.…”
Section: Photoluminescence (Pl) Spectramentioning
confidence: 59%
“…However, we demonstrated that the dopingenhanced activity may in fact have its origin in certain bulk properties of CdS instead of the charge transfer processes mentioned above [23]. Moreover, shallow surface states or inter-bandgap charge trapping sites, which arose from the doping of an impurity, were found to be important [11,13]. We point out that not many studies have investigated how the preparation-conditionedependent morphology and structural properties contribute to the water splitting activity of a semiconductor such as CdS.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…[3][4][5] It has been known that the control over the synthesis of CdS with certain morphologies plays a key role in their photocatalytic properties. [6][7][8] In addition, it was reported that the incorporation of Zn element into CdS to form CdZnS solid solution can result in enhanced photocatalytic activity for H 2 production relative to pure CdS via tuning the CdS bandgap width and band-edge position. [9][10][11] In addition, the combination of a suitable semiconductor with CdZnS can also result in a high photocatalytic activity.…”
Section: Introductionmentioning
confidence: 98%